ENERGY-SAVING USED COOKING OIL ROCKET STOVE DESIGN WITH INTEGRATED BLOWER FAN AND SOLAR POWERED (PLTS) - Vontas Alfeny Nahan; Topan Eka Saputra; Wiratno Y Sigin; Frans Putra Ganesa; Adhitya Ferdi Hari (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
The issue of energy availability and household waste is a significant issue that continues to grow with population growth and global energy consumption. Furthermore, household waste, such as used cooking oil and used cooking oil, is often disposed of carelessly into waterways or the surrounding environment. This causes soil and water pollution and can even damage micro-ecosystems in domestic environments. One relevant technological innovation is the development of a used cooking oil-fueled stove. This technology allows households to convert waste into heat energy for cooking. Therefore, an adequate air circulation system, such as a blower fan, is required to improve the mixing of air and oil during combustion. The research was conducted in the Mechanical Engineering Education Laboratory, Faculty of Teacher Training and Education, Palangka Raya University, by combining the use of used cooking oil as fuel and solar energy as a power source for the blower fan, reflecting the synergy between these two forms of renewable and sustainable energy. Specific plans and targets include publication of this research in a SINTA-accredited journal, HKI, and a research video.